Evolution of polyphenolic, anthocyanin, and organic acid components during coinoculation fermentation (simultaneous inoculation of LAB and yeast) and sequential fermentation of blueberry wine. Issue 11 (18th October 2022) - Zhang, Jigang; Fang, Ling; Huang, Xudong; Ding, Zhien; Wang, Chuyan
Abstract : Abstract: This research aims to investigate the effects of both sequential fermentation and coinoculation fermentation with yeast and lactic acid bacterial (LAB) on the dynamics of changes in basic quality parameters and organic acid, anthocyanin, and phenolic components as well as antioxidant activity during the fermentation of blueberry. The coculture‐fermented blueberry wine showed significant decreases in total phenolics, flavonoids, and anthocyanins, by 23.9%, 15.9%, and 13.7%, respectively, as compared with those before fermentation Fermentation changed the contents of organic acids in each group, with a more than 7‐fold increase in lactic acid contents as well as a more than 4‐fold reduction in quinic acid and malic acid contents. The content of all investigated anthocyanins first increased and then decreased. Moreover, different fermentation strategies exerted a profound influence on the dynamic change in phenolic components during fermentation; specifically, most of the phenolic acids showed a trend of increasing first, then decreasing, and finally increasing. Gallic acid, p‐coumaric acid, quercetin, and myricetin were increased by 116.9%, 130.1%, 127.2% and 177.6%, respectively, while syringic acid, ferulic acid, cinnamic acid, and vanillic acid were decreased by 49.5%, 68.5%, and 37.1% in sequentially fermented blueberry wine. Coinoculation fermentation with yeast and LAB produces faster dynamic variations and higher organic acid, anthocyanin, and phenolic profiles than sequential inoculation fermentation. Practical Application: In this work, brewing technology of sequential fermentation and coinoculation fermentation with yeast and LAB ( Lactobacillus plantarum SGJ‐24 and Oenococcus oeni SD‐2a) was adopted to ferment blueberry wine. This is an innovative technology of fruit wine brewing technology to produce wine products. Compared with traditional sequential brewing, simultaneous inoculation brewing can significantly accelerate the brewing process of fruit wine and slightly improve the quality of fruit wine in terms of active ingredients.